Microencapsulated sodium butyrate reduces the frequency of abdominal pain in patients with irritable bowel syndrome. (25th January 2013) - Banasiewicz, T.; Krokowicz, Ł.; Stojcev, Z.; Kaczmarek, B. F.; Kaczmarek, E.; Maik, J.; Marciniak, R.; Krokowicz, P.; Walkowiak, J.; Drews, M.
Abstract Aim Abdominal pain, defaecation disorder and change of bowel habit are the commonest symptoms of irritable bowel syndrome (IBS). The effect of microencapsulated sodium butyrate (MSB) was assessed on the severity of symptoms in patients with IBS. Method Sixty‐six patients treated with one of the standard pharmacological therapies for at least 3 months were included in the study. They were randomized to receive MSB as a supplemental treatment to standard therapy or to receiving a placebo. Previous pharmacological therapy was continued throughout the study in both arms. Clinical evaluation was performed at baseline, 4 and 12 weeks. Each assessment was documented by a validated visual analogue score questionnaire measuring the severity of selected clinical symptoms, a closed‐end questionnaire measuring the frequency of selected clinical symptoms and a single closed‐end question measuring the subjective improvement of symptoms. Results After 4 weeks there was a significant decrease of pain during defaecation in the MSB group which extended to improvement of urgency and bowel habit at 12 weeks. Reduction of abdominal pain, flatulence and disordered defaecation was not statistically significant. Conclusions MSB as a supplemental therapy can reduce the frequency of selected clinical symptoms in patients with IBS, without significant influence on reducing symptom severity.